2022
DOI: 10.1186/s12875-022-01946-x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, experiences, and attitudes of Australian General Practitioners towards medicinal cannabis: a 2021–2022 survey

Abstract: Background Medicinal cannabis (MC) products have been available on prescription in Australia for around six years. General practitioners (GPs) are at the forefront of MC prescribing and recent years have seen substantial increases in prescription numbers. This study examined the current knowledge, experiences, and attitudes of Australian GPs around MC. We also compared our findings to those of an earlier 2017 investigation. Method We conducted a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…The differences in main condition treated between prescribed and illicit users may stem from prescribed users’ receiving guidance from trained health professionals whose job is to be informed about the existing evidence for clinical indications for medications. Results from a recent survey of n = 505 Australian general practitioners support this interpretation, with respondents indicating they are much less comfortable with the idea of prescribing cannabis for anxiety, depression and sleep conditions than they are for pain, epilepsy, and chemotherapy-induced nausea [ 21 ]. Alternatively, it may be that the type of person who is already well-informed about the clinical evidence for effectiveness of cannabis for certain conditions is also more likely to seek their medical cannabis through legal channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in main condition treated between prescribed and illicit users may stem from prescribed users’ receiving guidance from trained health professionals whose job is to be informed about the existing evidence for clinical indications for medications. Results from a recent survey of n = 505 Australian general practitioners support this interpretation, with respondents indicating they are much less comfortable with the idea of prescribing cannabis for anxiety, depression and sleep conditions than they are for pain, epilepsy, and chemotherapy-induced nausea [ 21 ]. Alternatively, it may be that the type of person who is already well-informed about the clinical evidence for effectiveness of cannabis for certain conditions is also more likely to seek their medical cannabis through legal channels.…”
Section: Discussionmentioning
confidence: 99%
“…The dramatic increase in prescriptions reflects changing attitudes among doctors towards medical cannabis. Recent surveys and meta-analyses indicate that health professionals in Australia and the rest of the world are increasingly positive in their attitudes towards medical cannabis [ 21 25 ]. However, many clinicians remain concerned about their lack of experience prescribing; the increase in prescribing for conditions where there is limited empirical evidence for efficacy, such as mental health and sleep conditions; and the potential for harm to patients and society generally due to inappropriate prescribing [ 24 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36] In accordance with the findings of other studies, our participants agreed that MC education and training are imperative to improve understanding and preparedness to discuss MC in clinical settings. 37,38 The MC information sheet developed by the Best Practice Advocacy Centre New Zealand may support health professionals to facilitate MC discussions and prescribe confidently. 39 Research suggests experienced and educated cannabis prescribers may be better placed to evaluate the benefits and harms of prescribing cannabis, and discuss the trade-offs with patients.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study of family physicians demonstrated they were often hesitant to guide patients on medical cannabis use, including a reluctance to authorise its use, due to concerns about the potential for harm and a feeling they lacked education about its therapeutic benefit 42. Studies conducted in other jurisdictions and with other specialties have reported similar findings 43 44…”
Section: Discussionmentioning
confidence: 99%